ETHICAL PLURALISM IN ACTION: TRANSLATING GUS DUR’S NORMATIVE FRAMEWORK INTO INTERFAITH CIVIC PRAXIS - Nanda Khairiyah; Siti Nabilah (Peminat Ilmu Ushuluddin, 2025)
This article examines how Abdurrahman Wahid’s (Gus Dur) ethical vision of religious pluralism is translated from a normative framework into lived social praxis within contemporary interfaith contexts. While existing studies have largely focused on Gus Dur’s intellectual, theological, and political contributions, the practical enactment of his pluralist ideas at the grassroots level remains underexplored. Addressing this gap, the study employs a qualitative ethnographic approach to investigate how core principles of equality (musāwah), justice (ʿadl), and freedom of belief (ḥurriyyah al-iʿtiqād) are embodied in everyday interfaith engagements. Fieldwork was conducted within interfaith communities that consciously draw on Gus Dur’s legacy, with the Forum for Religious Harmony (FKUB) in Jakarta serving as an empirical lens. Data were collected through participant observation, in-depth interviews, and documentation. The findings reveal a significant transformation of pluralism from abstract discourse into a lived civic ethic, manifested in interfaith rituals, conflict mediation, inclusive education, and digital activism. These practices are sustained through dialogical, collaborative, and affective relational patterns among interfaith actors. This study argues that Gus Dur’s pluralism operates not merely as a theological doctrine, but as a dynamic framework of civic engagement rooted in local wisdom and social interaction. By foregrounding ethnographic insights, the article contributes to global discussions on religious pluralism by demonstrating how ethical values can be operationalized as socially embedded and context-sensitive practices in plural societies.